Primary dexamethasone treatment of multiple myeloma - Alexanian, R.; Dimopoulos, M.A.; Delasalle, K.; Barlogie, B. (Blood, 1992)
Intermittent courses of dexamethasone (DEX) were administered to 112 consecutive, previously untreated patients with multiple myeloma (MM). Using criteria based on a 75% or greater reduction of calculated tumor mass, the overall response rate was 43%. Among comparable patients, response rates were approximately 15% less than those observed previously with vincristine-doxorubicin by continuous infusion with intermittent DEX (VAD) and similar to those with melphalan-prednisone. The projected survival times with VAD or DEX were similar. Results indicated that DEX accounted for most of the plasma cell reduction achieved with VAD. Serious complications occurred in 27% of patients treated with VAD, but in only 4% of those who received DEX. In view of the similar outcome with fewer serious complications, DEX provided a simple, effective, and safe primary treatment for a large fraction of patients with MM. Patients who appear most likely to benefit include those with hypercalcemia or pancytopenia, or who require simultaneous radiotherapy for a pathologic fracture. © 1992 by The American Society of Hematology.